Peran Internet Berbasis Dakwah Islam Dalam Menguatkan Akidah Ummat - Efendi, Erwan; Zihad, Aidil; Panggabean, Armaini (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Multimedia has an important role in strengthening and enhancing the faith of the people. Multimedia will also support the da'wah process carried out by the preachers. Multimedia is the use of computers to create and combine text, graphics, audio, moving images (video and animation). Along with the times, of course the existing technology is also increasingly sophisticated, one of which is the internet. That way, da'wah is not only conveyed orally. However, da'wah carried out through writing by utilizing multimedia will become more urgent and effective. This study aims to strengthen the faith of the ummah through Islamic da'wah by utilizing existing multimedia. This research uses the type of research in the form of library research (library research). In collecting data, researchers used books and journals related to theoretical studies and supported by several scientific references. The data collection technique was carried out using the content analysis method. The results of this study have shown that the role of multimedia (internet) which is used based on Islamic da'wah can strengthen the faith of the ummah because the use of the internet as a medium for preaching is very effective, this is supported by the nature of the internet which is not limited by space and time. Through this research, it is hoped that it will contribute ideas to inspire preachers to use multimedia as a means of conveying da'wah messages. Keyword: Multimedia, Islamic Da'wah, Ummah Foundation